2008
DOI: 10.1002/bimj.200710415
|View full text |Cite
|
Sign up to set email alerts
|

Youden Index and Optimal Cut‐Point Estimated from Observations Affected by a Lower Limit of Detection

Abstract: SummaryThe receiver operating characteristic (ROC) curve is used to evaluate a biomarker's ability for classifying disease status. The Youden Index (J), the maximum potential effectiveness of a biomarker, is a common summary measure of the ROC curve. In biomarker development, levels may be unquantifiable below a limit of detection (LOD) and missing from the overall dataset. Disregarding these observations may negatively bias the ROC curve and thus J. Several correction methods have been suggested for mean esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
673
0
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 984 publications
(685 citation statements)
references
References 20 publications
3
673
0
9
Order By: Relevance
“…The Youden Index is a receiver operating curve (ROC) summary statistic that optimizes a biomarker's differentiating ability by giving equal weight is given to sensitivity and specificity (Ruopp et al, 2008). In the present study, we compared the Youden Index of different methods of screening, and found that the Youden Index of combined testing was markedly higher than that of the Pap test and the TCT, but the Youden Index of the Pap test was comparable with that of the TCT.…”
Section: Discussionmentioning
confidence: 73%
“…The Youden Index is a receiver operating curve (ROC) summary statistic that optimizes a biomarker's differentiating ability by giving equal weight is given to sensitivity and specificity (Ruopp et al, 2008). In the present study, we compared the Youden Index of different methods of screening, and found that the Youden Index of combined testing was markedly higher than that of the Pap test and the TCT, but the Youden Index of the Pap test was comparable with that of the TCT.…”
Section: Discussionmentioning
confidence: 73%
“…The Youden index (J), a main summary statistic of the ROC curve defined as J = max (c) [sensitivity (c)+specificity (c)−1], was employed to determine the optimal cutoff (c*). This was defined as the value that optimizes the ARR's dis criminating ability in that it corresponds to the highest average of sensitivity and specificity [23]. The significance was set at p < 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal cut-off values for FC concentration for assessment and prediction of endoscopic recurrence were determined using logistic regression in combination with the senspec command in STATA12 and Youden Index. 33,34 There were three cohorts used for analysis:…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%